Landform and phosphorus effects on nitrogen fixed by annual clovers and its contribution to succeeding cereals in the Ethiopian highlands - Haque, I.; Lupwayi, N.Z. (1999)
Poor drainage of Vertisols and nitrogen (N) and phosphorus (P) deficiencies are some if the major constraints to food and feed production in the Ethiopian highlands. The effects of soil drainage and P supply on N fixation by annual trifolium species and their residual value to succeeding crops was investigated in field experiments on Vertisols at Addis Ababa and Ginchi. In one experiment, the Trifolium spfixed 55-122 kg N/ha when P fertiliser was applied, and the increase in grain yields of oats following different clovers ranged from 20 percent for T. steudneri to 55 percent for T. rueppellianum compared with yields of continuous oats. In another experiment, landform treatments designed to effect drainage had no significant effects on N fixation and clover dry matter, or on yields of wheat following the clovers. Phosphorus applied at 50 kg P/ha increased N fixation from 11 to 72 kg N/ha on the broadbed-and-furrow landform and from 10 to 64 kg N/ha on the flat landform, and herbage yield responded similarly. Only the wheat following P-applied clover, particularly when supplemented with N fertiliser at 50 kg N/ha, had significantly higher wheat grain yields compared with continuous wheat grown without N fertiliser. These results confirm the critical importance of P increasing the productivity of clovers in the Ethiopian highlands.